Influence of potassium on the quality of grains and seeds of flooded rice - Grohs, Mara; de Moura Silveira, Rodrigo; Fumagalli Miranda, Fernando; Doring Wolter, Roberto Carlos; Bredow, Alex Alan; Zabot, Giovani Leone; Tres, Marcus Vinícius (Acta Iguazu, 2020)
Potassium can influence the productivity and the physical and physiological qualities of grains and seeds of flooded rice, although its influence is not clear yet. Based on the necessity of more information, this work presents the evaluation of different stages of potassium application on rice grains productivity, physical quality (whole grain and chalk kernel) and seed physiological quality (vigor and germination). The results show that the potassium fertilization has an influence on the physical quality of rice grains. When performed near to the reproductive stage, it can increase the percentage of whole grains and decrease the chalk kernel index. For producing seeds, all fertilization should be done up to the V3 stage in order to increase the seed vigor.